Figurative Language in Taylor Swift Folklore Album - Haliza, Azzahra (Papanda Publisher, 2025)
This study explores the application of figurative language in the Folklore album by Taylor Swift and examine its relevance to language and literature education. The objective is to determine the kinds and interpretations of figurative expressions within selected tracks and to analyze how they can be utilized in academic settings. Adopting the descriptive qualittaive approach, the researchers examined seven songs from the album: My Tears Ricochet, Cardigan, The 1, Illicit Affairs, Invisible String, Exile, and August. The lyrics were sourced from official lyric websites and assessed according to categories of figurative language, including metaphor, simile, hyperbole, personification, irony, and allusion. Results indicate that metaphor appears as the most frequently used device. The figurative elements in the songs successfully communicate deep emotions and personal stories, enhancing the emotional and literary engagement of listeners. In addition, the study emphasizes the educational value of incorporating popular song lyrics to foster students critical analysis, emotional awareness, and interpretative abilities. This research also reinforces the use of music as an effective and interactive tool for teaching literary techniques, contributing to the advancement of modern and student-centered educational strategies in language and literature.